Discordant Expression of Tissue Factor Antigen and Procoagulant Activity on Human Monocytes Activated with LPS and Low Dose Cycloheximide - Walsh, John D; Geczy, Carolyn L (Thrombosis and Haemostasis, 1991)
The mechanisms underlying the superinduction of procoagulant activity by cycloheximide (CHX) on LPS-activated human monocytes have been investigated. Tissue factor (TF) activity of intact, viable cells was quantitated with a plasma recalcification assay and assays using chromogenic substrates specific for thrombin and factor Xa (FXa). TF antigen was measured simultaneously by immunocytochemical staining and immunoblotting with an anti-TF monoclonal antibody (MAb). Peripheral blood mononuclear cells (PBMC) activated with LPS in the presence of low dose CHX expressed more TF activity (approx. 100% increase) than cells activated with LPS alone. However, TF antigen levels were decreased approximately 70% by CHX. This discordant relationship was due primarily to differences in rates of activation of factor X (FX); LPS/CHX-treated PBMC activated nearly twice as much FX as LPS-treated cells (2.19 ± 0.37 versus 1.10 ± 0.21 ng FXa/106 PBMC/min, respectively). These studies indicate that TF cofactor activity on LPS/CHX-treated monocytes was approximately 7 times greater than that present on LPS-treated cells. Increased TF functional activity may be due to CHX-induced alterations in the type and content of phospholipids (PL) in the cell membrane. Results showed that exogenous mixed PL markedly increased TF activity on LPS-activated monocytes, but not on LPS/CHX-activated cells, without increasing TF antigen levels or altering cell viability. Membrane alterations may occur on monocytes in certain pathological or iatrogenic conditions resulting in a highly active form of TF in vivo.